EVALUASI TINGKAT PELAKSANAAN TUGAS PENYULUH PERIKANAN BANTU DALAM MEMBINA PETAMBAK DI KECAMATAN MUARA JAWA KABUPATEN KUTAI KARTANEGARA - Enny Adhanasti; Helminuddin; Fitriyana (Jurnal Pembangunan Perikanan dan Agribisnis, 2020)
The purposed of this study was to determine the level of implementation of the task of assisting fisheries instructors in fostering farmers in Muara Jawa District, Kutai Kartanegara Regency. This research was conducted in Muara Jawa District for 9 months starting in February - October 2019. The collection of primary data in this study was conducted by observation and direct interviews with respondents using a questionnaire. Secondary data in the form of documents that support research carried out by means of literature study. Determination of the sample using Purposive Sampling and Systematic Sampling methods with total sample of 57 fish farmers. Data is presented in tabular form and processed in quantitative descriptive manner, each question is given a score based on the Likert Scale. The results showed that the level of implementation of the task of extension fisheries instructors in Muara Jawa District Kutai Kartanegara Regency was included in the high category with a score of 75.49, in the range of 70.1 - 90.0, which means the task of assisting fisheries instructors in Muara Jawa District had been running well. Keywords: fisheries extension instructors, fish farmers, muara jawa